Development of A Local Culture based Bilingual Book Heritage Model in Maluku - Ratumanan, Stelie Dorce; Sunendar, Dadang; Damayanti, Vismaia (Proceedings International Conference on Education Innovation and Social Science, 2024)
Efforts to preserve regional languages using a bilingual inheritance model are prioritized for language speakers themselves, especially the next generation who are starting to be exposed to globalization and therefore tend to forget regional languages and literature. If we look at the level of language threat, it starts from safe, vulnerable/unsafe, threatened, seriously threatened, threatened with extinction, even extinct or lost. In the Maluku area itself, it can be categorized as threatened to endangered. The inheritance model is carried out to pass on regional languages to the next generation as speakers of regional languages in order to save, preserve and transfer regional languages as heirs. This research aims to produce a model for the inheritance of bilingualism based on local culture in Maluku in the form of bilingual books and validate the feasibility of local culture-based folklore books for educational circles and the community in Maluku. The method used in this research is research and development (R&D). The model used in this research is a 4-D model (four-D model) which consists of 4 stages, namely (1) defining, (2) designing, (3) developing, and ( 4) disseminate (disseminate). The results of the material/content expert validation percentage were 93% (very valid), the language expert validation percentage was 93% (very valid) and the percentage of design experts was 95%. This shows that the product has passed the validation stage and is ready to be tested in the field because it meets the assessment criteria. After carrying out product trials, the following percentage results were found: (1) trial results. Small group student responses with an average value of 78.8%. The results of the student response analysis in the field trial were 94% (very practical) and the results of the teacher's response test in the field received a score of 79 (very practical).